Bottoms up. (Economist, 2013)
The article considers economic conditions and policy in China. Research by economics Jonathan Gardner and Helen Qiao of the investment banking firm Morgan Stanley which concludes that consumption in China is a far larger share of the country's gross domestic product (GDP) than government statistics report is discussed in relationship to concerns that China's official economic indicators are manipulated by the government for political reasons.